Within-host temporal fluctuations of Trypanosoma cruzi discrete typing units: the case of the wild reservoir rodent Octodon degus - Rojo, Gemma (Parasit Vectors, 2017)
BACKGROUND: Chagas disease caused by Trypanosoma cruzi is considered a major public health problem in America. After an acute phase the disease changes to a chronic phase with very low parasitemia. The parasite presents high genetic variability with seven discrete typing units (DTUs): TcI-TcVI and Tc bat. The aim of this work is to evaluate fluctuation of parasitemia and T. cruzi DTUs in naturally infected Octodon degus. METHODS: After animal capture parasitemia was obtained by qPCR and later the animals were evaluated by three serial xenodiagnoses using two insect vector species, Mepraia spinolai and Triatoma infestans. The parasites amplified over time by insect xenodiagnosis were analyzed by conventional PCR and after that the infective T. cruzi were characterized by means of hybridization tests. RESULTS: The determination of O. degus parasitemia before serial xenodiagnosis by qPCR reveals a great heterogeneity from 1 to 812 parasite equivalents/ml in the blood stream. The T. cruzi DTU composition in 23 analyzed animals by xenodiagnosis oscillated from mixed infections with different DTUs to infections without DTU identification or vice versa, this is equivalent to 50% of the studied animals. Detection of triatomine infection and composition of T. cruzi DTUs was achieved more efficiently 40 days post-infection rather than after 80 or 120 days. CONCLUSION: Trypanosoma cruzi DTUs composition fluctuates over time in naturally infected O. degus. Three replicates of serial xenodiagnosis confirmed that living parasites have been studied. Our results allow us to confirm that M. spinolai and T. infestans are equally competent to maintain T. cruzi DTUs since similar results of infection were obtained after xenodiagnosis procedure.